Diffusion-Tensor Imaging for the Detection and Quantification of Treatment-Induced White Matter Injury in Children with Medulloblastoma: A Pilot Study - Khong, Pek-Lan; Kwong, Dora L. W.; Chan, Godfrey C. F.; Sham, Jonathan S. T.; Chan, Fu-Luk; Ooi, Gaik-Cheng (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Treatment-induced white matter (WM) injury in medulloblastoma survivors, as manifested by deterioration of cognitive function, is prevalent. However, no reliable imaging method exists for early detection and quantification. Our goal was to determine whether anisotropy of WM is reduced in medulloblastoma survivors and whether fractional anisotropy (FA) can be used as an index for evaluation of treatment-induced WM injury.METHODS: We evaluated nine medulloblastoma survivors treated with surgery, cranial irradiation, and chemotherapy by use of diffusion-tensor (DT) imaging and compared FA findings in selected WM sites (cerebellar hemispheres, pons, medulla oblongata, frontal periventricular WM, parietal periventricular WM, and corona radiata) with those of healthy age-matched control subjects. FA maps were compared with conventional T2-weighted images. FA was also compared with age at treatment, time interval since treatment, and deterioration of school performance. The two-tailed paired t test was used to determine statistical significance (P < .05).RESULTS: Significant reduction of FA (P < .05) was seen in all anatomic sites in the patient group compared with FA in control subjects, except in the frontal periventricular WM, even in areas with normal appearance on T2-weighted images. FA reduction ranged from 12.4–19% (mean, 16.5%). Compared with control subjects, posterior fossa and supratentorial WM FA in patients were reduced by 14.6% (SD 1.9%) and 18.4% (SD 0.55%), respectively (P = .029). Reduction of supratentorial WM FA correlated with younger age at treatment (< 5 years), longer interval since treatment (> 5 years), and deterioration of school performance.CONCLUSION: DT imaging and use of the index FA is potentially useful for early detection and monitoring of treatment-induced WM injury in children with medulloblastoma.